Impact of incremental versus conventional initiation of haemodialysis on residual kidney function: study protocol for a multicentre feasibility randomised controlled trial. Issue 8 (13th August 2020) - Kaja Kamal, Raja Mohammed; Farrington, Ken; Wellsted, David; Sridharan, Sivakumar; Alchi, Bassam; Burton, James; Davenport, Andrew; Vilar, Enric
Abstract : Introduction: Preserving residual kidney function (RKF) may be beneficial to patients on haemodialysis (HD) and it has been proposed that commencing dialysis incrementally rather than three times a week may preserve RKF. In Incremental HD, target dose includes a contribution from RKF, which is added to HD dose, allowing individualisation of the HD prescription. We will conduct a feasibility randomised controlled trial (RCT) comparing incremental HD and conventional three times weekly treatments in incident HD patients. The study is designed also to provide pilot data to allow determination of effect size to power a definitive study. Methods and analysis: After screening to ensure native renal urea clearance >3 mL/min/1.73 m 2, the study will randomise 54 patients within 3 months of HD initiation to conventional in-centre thrice weekly dialysis or incremental in-centre HD commencing 2 days a week. Subjects will be followed up for 12 months. The study will be carried out across four UK renal centres. The primary outcome is to evaluate the feasibility of conducting a definitive RCT and to estimate the difference in rate of decline of RKF between the two groups at 6 and 12 months time points. Secondary outcomes will include the impact of dialysis intensity on vascular access events, major adverse cardiac events and survival. Impact of dialysis intensity on patient-reported outcomes measures, cognition and frailty will be assessed using EQ-5D-5L, PHQ-9, Illness Intrusiveness Rating Score, Montreal Cognitive assessment and Clinical Frailty Score. Safety outcomes include hospitalisation, fluid overload episodes, hyperkalaemia events and vascular access events. This study will inform the design of a definitive study, adequately powered to determine whether RKF is better preserved after incremental HD initiation compared with conventional initiation. Ethics and dissemination: Ethics approval has been granted by Cambridge South Research Ethics Committee, United Kingdom(REC17/EE/0311). Results will be disseminated via peer-reviewed publication. Trial registration number: NCT03418181